Fundamental Properties of Phenylboronic‐Acid‐Coated Gate Field‐Effect Transistor for Saccharide Sensing. Issue 10 (1st September 2014) - Kajisa, Taira; Sakata, Toshiya
Abstract We report the surface and electrical characteristics of a phenylboronic acid (PBA)‐coated gate field effect transistor (FET) biosensor for a highly sensitive detection of various saccharides. 4‐mercaptophenylboronic acid (MPBA) was self‐assembled on a Au extended‐gate electrode, which was used as a saccharide recognition substrate of the PBA–FET. The binding affinity of PBA with various monosaccharides and disaccharides were evaluated by the amount of voltage changes on the Au gate surface in response to sugar concentrations using the PBA–FET. The specific diol‐binding of PBA with saccharides induces molecular charges onto PBA, resulting in the detection of charges at a lower concentration of 50 μM. In particular, the binding affinities of PBA with the saccharides contributes to the different electrical signals. The platform based on the PBA–FET is useful for a convenient and highly sensitive detection of various saccharides in the fields of food engineering and medicine.